Analisis Motivasi Kerja, Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan Dimediasi Kepuasan Kerja pada Angkatan Kerja Generasi Z - Gilang Pratama Hafidz; Mega Noviyati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze work motivation, transformational leadership and organizational culture on employee performance mediated by job satisfaction in the generation Z workforce. This research is a quantitative research using non-probability sampling method with 325 respondents. Based on the results of data analysis, it can be concluded that work motivation on job satisfaction does not have a positive effect, organizational culture has the largest positive influence on the performance of Generation Z employees, transformational leadership style and work motivation have a positive influence on the performance of Generation Z employees and then job satisfaction is proven to mediate the three exogenous variables on employee performance.